L’ego intermédiaire ou l’authentification de la terreur - Lifschutz, Vladimir (Romanica Silesiana)
The article offers an analysis on the mechanisms of fear in movies. How does a fictional work manage to inspire emotion? It is our question here. Starting from Walton’s theories, we offer to understand the connections that are created between the viewer and the work itself. Moreover, we explore how a movie can be recognized by the viewer through the process of authentification. It is precisely the matter at hand: fear in movies is the result of a connection between the viewer and a fictional universe. Through the examination of the links between those two, we can reveal how fear works in a certain type of narrative. Key words : fear, ego, fictionnal worlds, fiction, game, authentification